A new species of Camelobaetidius Demoulin, 1966 (Ephemeroptera: Baetidae), from the Colombian Orinoco River basin - Salinas-Jimenez, Luis Gonzalo; Boldrini, R.; Osorio-Ramirez, Diana Paola; Caro, Clara Ines; Rojas-Peña, Jose Ismael (Zootaxa, 2019)
Three species of Camelobaetidius Demoulin, 1966 have been reported from Colombia until now, based on nymphs. We describe a fourth species based on nymphs from the Colombian Orinoco river basin. The new species can be recognized by: 1) labrum narrowly rounded anteriorly; 2) segment II of labial palp with a short rounded distomedial projection; 3) incisors of right mandible with eleven denticles; 4) gills absent from the bases of coxae; 5) tarsal claws with ten denticles; 6) outer margin of forefemur with a row of about 23 long, spine-like setae; 7) posterior margin of tergum IV with truncate spines, and 8) terminal filament almost as long as cerci. [Zoobank URL: urn:lsid:zoobank.org:act:500CF998-8EF3-43E3-BA8B-F062B92768F3]